Efficacy of Extracorporeal Shock Wave Therapy for the Treatment of Chronic Pelvic Pain Syndrome: A Randomized, Controlled Trial. (28th August 2013) - Vahdatpour, Babak; Alizadeh, Farshid; Moayednia, Amir; Emadi, Masoud; Khorami, Mohammad Hatef; Haghdani, Saeid
Abstract : Objectives . To investigate the effectiveness of extracorporeal shock wave therapy (ESWT) for symptoms alleviation in chronic pelvic pain syndrome (CPPS). Materials and Methods . 40 patients with CPPS were randomly allocated into either the treatment or sham group. In the first group, patients were treated by ESWT once a week for 4 weeks by a defined protocol. In the sham group, the same protocol was applied but with the probe being turned off. The follow-up assessments were done at 1, 2, 3, and 12 weeks by Visual Analogue Scale (VAS) for pain and NIH-developed Chronic Prostatitis Symptom Index (NIH-CPSI). Results . Pain domain scores at follow-up points in both treatment and sham groups were reduced, more so in the treatment group, which were significant at weeks 2, 3, and 12. Urinary scores became significantly different at weeks 3 and 12. Also, quality of life (QOL) and total NIH-CPSI scores at all four follow-up time points reduced more significantly in the treatment group as compared to the sham group. Noticeably, at week 12 a slight deterioration in all variables was observed compared to the first 3 weeks of the treatment period. Conclusions . our findings confirmed ESWT therapy as a safe and effective method in CPPS in short term.